Crack closure effect during the impact coal seam with high-pressure air blasting and the influence of gas drainage efficiency - Weihua Song; Weihua Song; Huice Jiao; Yingwei Wang (Frontiers in Earth Science, 2023)
The crack closure in impact coal seams induced by high-pressure air blasting greatly affects gas drainage efficiency. The length of the crack closure was calculated and analyzed based on energy and elastic theories. The closure region was then determined to be 3.8 m from the blasting hole. The results of a high-pressure air blasting experiment in the underground of one coal mine in China showed that the effect of crack closure on gas drainage efficiency manifested as a decreased amplitude of gas emission in the crack closure region. At 1.0–4.0 m from the blasting hole, the amplitude of gas emission in the observation holes first increased and then decreased with increasing distance from the blasting hole. At 1.8–2.5 m from the blasting hole, the amplitude of the gas emission was maximal. At 4.0 m from the blasting hole, the crack was nearly closed, and the gas emission in the observation holes was minimal. The theoretical calculation had good consistency with the field test results; thus, it can provide an important reference for an appropriate arrangement of gas drainage boreholes.